2011
DOI: 10.1158/0008-5472.can-10-0714
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Kras Promotes Chemotherapy-Induced Growth Factor Shedding via ADAM17

Abstract: Oncogenic mutations in Kras occur in 40% to 45% of patients with advanced colorectal cancer (CRC). We have previously shown that chemotherapy acutely activates ADAM17, resulting in growth factor shedding, growth factor receptor activation, and drug resistance in CRC tumors. In this study, we examined the role of mutant Kras in regulating growth factor shedding and ADAM17 activity, using isogenic Kras mutant (MT) and wild-type (WT) HCT116 CRC cells. Significantly higher levels of TGF-a and VEGF were shed from K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 29 publications
(49 reference statements)
2
41
1
1
Order By: Relevance
“…31,32) Moreover, in HUVECs, it has been already reported that PKCα is involved in the regulation of VEGF 35) the one is mediated by TACE. 36,37) These results show that PKCα or PKCβ may be involved in the mechanism of TACE-mediated EPCR shedding induced by PMA, although further study is necessary. We have known that PKC translocation is a sign of PKC activation.…”
Section: Discussionmentioning
confidence: 82%
“…31,32) Moreover, in HUVECs, it has been already reported that PKCα is involved in the regulation of VEGF 35) the one is mediated by TACE. 36,37) These results show that PKCα or PKCβ may be involved in the mechanism of TACE-mediated EPCR shedding induced by PMA, although further study is necessary. We have known that PKC translocation is a sign of PKC activation.…”
Section: Discussionmentioning
confidence: 82%
“…ADAM17 activity is also increased on cellular treatment with chemotherapeutic agents (40,41) and ADAM17 activation by the antimetabolite 5-FU and the topoisomerase I inhibitor SN-38 primarily occurs in a Kras-mutated background and via the MAP/ERK kinase pathway. Our results demonstrate that irradiation promotes ADAM17 activation, but in a furinmediated way and interestingly, in both Kras-wild-type (NCI-H125, CALU-3) and Kras-mutated NSCLC cell lines (A549, H460).…”
Section: Discussionmentioning
confidence: 99%
“…32,No. 8 In addition to regulation at the transcriptional level, ADAM17 activity is controlled post-translationally in cancer cells by oncogenic ras, src and v-src, which leads to increased shedding of the ErbB ligand TGFa [32,33]. In addition, activated ADAM17 and subsequent ErbB transactivation can mediate resistance to chemotherapy [34].…”
Section: Reviewmentioning
confidence: 99%
“…Modification of disulfide Review Trends in Immunology August 2011, Vol. 32,No. 8 bonding was achieved by inactivation of extracellular protein disulfide isomerases (PDIs).…”
Section: Regulation Of Adam17 Activitymentioning
confidence: 99%
See 1 more Smart Citation